COMPARISON OF UMBILICAL CORD BLOOD LIPID PROFILE IN TERM AND PRETERM NEONATES: A CROSS-SECTIONAL STUDY AT A TERTIARY CARE HOSPITAL IN CENTRAL INDIA - Dr. Adarsh Arvind Gandhe; Dr. Apurva Ganesh Kale; Dr. Pratibha Vinay Kale; Dr. Sanket Santosh Pande (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Changes in foetal lipid profiles have been connected to an increased risk of cardiovascular disease in later life. Lipid metabolism starts in utero. Lipid transport and metabolism may be impacted by preterm delivery. The purpose of this study is to compare the lipid profiles of the umbilical cord blood in term and preterm newborns.Objectives: Estimating and contrasting the cord blood lipid profiles of term and preterm infants. Methods: From March 2022 to January 2023, a tertiary care hospital conducted a comparative cross-sectional study. 200 newborns (109 term, 91 preterm) had cord blood samples taken, and an autoanalyzer was used to measure the levels of total cholesterol, triglycerides, LDL, HDL, and VLDL. Version 20 of SPSS was used for statistical analysis.Results: The mean total cholesterol was 103.63 ± 21.09 mg/dL in preterm neonates and 72.44 ± 21.27 mg/dL in term neonates (p